River Ganges water as reservoir of microbes with antibiotic and metal ion resistance genes: High throughput metagenomic approach. (March 2019) - Reddy, Bhaskar; Dubey, Suresh Kumar
Abstract: The large scale usage of antibiotics and trace elements leads to their progressive release in the environment, and ultimately the spread of antibiotic resistance genes (ARGs) and metal ion resistance genes (MRGs) in bacteria. A high-throughput metagenomic sequencing of the microbial community in water and sediments in the river Ganges harboring resistance genes was performed. The results revealed that the river harbors a broad spectrum of resistance genes with high abundance in sediments. The highly dominant ARGs type was beta-lactam, multidrug/efflux and elfamycin. The ARGs such as ( tuf, parY, ileS, mfd ) were highly abundant in water and sediments. The MRGs subtype acn was the most abundant metal resistance gene in water and sediments. Majority of ARGs types showed significant (p ≤ 0.05) positive correlation with the MRGs types in the river environment suggesting their distribution and transfer to be possibly linked. Taxonomic classification revealed that Proteobacteria and Actinobacteria were the two most abundant phyla in water and sediments. Arcobacter, Terrimicrobium, Acidibacter and Pseudomonas were the most abundant genera. This study suggests that antibiotics and metals are the driving force for the emergence of resistance genes, and their subsequent propagation and accumulation in the environmental bacteria. The present metagenomic investigation highlights significance of such study, and attracts attention for the mitigation of pollutants associated with the propagation of ARGs and MRGs in the river environment. Graphical abstract: Image 1 Highlights: Study indicated that river Ganges is highly polluted by ARGs and MRGs. Metagenomic analysis detected 23 different types of ARGs and MRGs. Sediment was dominated with taxa, ARGs and MRGs resistance genes. Beta-lactam and multidrug resistance genes were the most abundant in river Ganges. Pseudomonas, Acinetobacter and Arcobacter were the most abundant genera.